Interaksi Komunikasi Dalam Dialog Drama Performance Class Mahasiswa Jurusan Bahasa Inggris STBA IEC JAKARTA (Suatu Kajian Etnografi Komunikasi) - sri arfani fani (Wanastra: Jurnal Bahasa dan Sastra, 2017)
This study is a study of ethnography communication. The purpose of this research is to know the phenomenon of communication interaction in performance drama class. Then can be known pattern of communication is in discourse analysis through approach of ethnography of communication.   The method of this study was descriptive content analysis. The procedure of data analysis and interpretation adapted pattern SPEAKING GRID model made by HYMES .The data were taken from the scenario of drama dialog in STIBA IEC Jakarta class. The findings in this study are the clarity of the content of the conversation that has a pattern in accordance with the requirements of the process. The topic and purpose of patterned conversation arose.  It was raised a new topic.The process of newtopic was finding from the act sequence. The results of the conversations was finding in the end of the dialog namely:  the dialog was need and provide information, the dialog was receive information, the dialog was having positive responses, the dialog was asking questions and providing answers. Based of the results of the dialog of speaking in the drama performance  has  change of the message and contents.